Rudy rides the rails : a Depression era story - Mackall, Dandi Daley (Sleeping Bear Press : Thomson/Gale, 2007)
In 1932, during the Depression in Ohio, thirteen-year-old Rudy, determined to help his family weather the hard times, hops a train going west to California and experiences the hobo life.